2017
DOI: 10.1016/j.otsr.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Successful outcome with minimally invasive plate osteosynthesis for periprosthetic tibial fracture after total knee arthroplasty

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Periprosthetic fractures of the tibia, or fractures below TKAs, are less common than periprosthetic fractures of the distal femur, with a prevalence of between 0.4 and 1.7% [1][2][3]. Many authors have reported several fixation options to treat these difficult fractures [4][5][6][7]. However, no consensus exists regarding the optimal fixation for periprosthetic tibial fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periprosthetic fractures of the tibia, or fractures below TKAs, are less common than periprosthetic fractures of the distal femur, with a prevalence of between 0.4 and 1.7% [1][2][3]. Many authors have reported several fixation options to treat these difficult fractures [4][5][6][7]. However, no consensus exists regarding the optimal fixation for periprosthetic tibial fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the fracture occurred in a patient with severe rheumatoid arthritis, osteoporosis, and heart failure. Kim et al reported that osteoporosis, such as that which occurs with old age, rheumatoid arthritis, and use of corticosteroids, is a risk factor for periprosthetic tibial fractures [4].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, even the postoperative CT found that the articular surface of the lateral tibial bone has not been well restored .At the same time, Ringus et al (11) found that compared with the tibial plateau articular surface collapse of less than 10mm, the tear of the lateral meniscus increased more than 10mm. Daniel Stahl et al (12) found that about 30% of the meniscus needed to be repaired during the operation, while Park HJ et al Performed 661 simultaneous repairs of the lateral tibial plateau and meniscus at the same time, and achieved good knee function after operation (13).Therefore, the current combination of C-arm machine and arthroscopy for the treatment of tibial plateau Schatzker III fractures has become a trend. Arthroscopic visualization surgery is a very beneficial technique.…”
Section: Technical Progress: 21 C-arm Machine and Arthroscopy Assistmentioning
confidence: 99%
“…In 2017, Kim et al [37] aimed to evaluate the effectiveness of the minimally invasive plate osteosynthesis (MIPO) technique with locking plates for periprosthetic tibial fractures after TKA. Their study covered 16 patients.…”
Section: Articles Covering Tibial Fractures After Tkamentioning
confidence: 99%